Empirical challenges from the comparative and developmental literature to the Shared Intentionality Theory – a review of alternative data on recursive mind reading, prosociality, imitation and cumulative culture - Sauciuc, Gabriela-Alina; Persson, Tomas (Frontiers in Psychology, 2023)
Humans have an irresistible inclination to coordinate actions with others, leading to species-unique forms of cooperation. According to the highly influential Shared Intentionality Theory (SITh), human cooperation is made possible by shared intentionality (SI), typically defined as a suite of socio-cognitive and motivational traits for sharing psychological states with others, thereby enabling individuals to engage in joint action in the mutually aware pursuit of shared goals. SITh theorises that SI evolved as late as 400,000 years ago, when our ancestors (in particular, Homo heidelbergensis) turned to a kind of food procurement that obligatorily required joint coordinated action. SI is, thus, hypothesized to be absent in other extant species, including our closest genetic relatives, the nonhuman great apes (“apes”). According to SITh, ape psychology is exclusively driven by individualistic motivations, as opposed to human psychology which is uniquely driven by altruistic motivations. The evolutionary scenario proposed by SITh builds on a series of findings from socio-cognitive research with apes and human children, and on the assumption that abilities expressed early in human development are human universals, unlikely to have been shaped by socio-cultural influences. Drawing on the primatological and developmental literature, we provide a systematic – albeit selective – review of SITh-inconsistent findings concerning psychological and behavioural traits theorised to be constitutive of SI. The findings we review pertain to all three thematic clusters typically addressed in SITh: (i) recursive mind reading; (ii) prosociality; (iii) imitation and cumulative culture. We conclude that such alternative data undermine two core SITh claims: the late evolutionary emergence of SI and the radical divide between ape and human psychology. We also discuss several conceptual and methodological limitations that currently hamper reliable comparative research on SI, in particular those engendered by Western-centric biases in the social sciences, where an overreliance on Western samples has promoted the formulation of Western-centric conceptualisations, operationalisations and methodologies.